Implementation of Discovery Learning Based Worksheet To Improve Students’ Concept Mastery of Science - Ceriasari, Bertiayu; Sunyono, Sunyono; Rudibyani, Ratu Betta (FKIP Universitas Lampung, 2019)
This study aims to determine the application of student worksheets based discovery learning to increase concept mastery student in the experimental class 1 and class 2 experiments. The method used is pre experimental design with one group pretest-posttest design to look at the increase in the value pretest and posttest in each class experiment. The results showed that through learning using student worksheets based discovery learning can improve students mastery of concepts with high category in the experimental class 1 and class 2 experiments with each N-gain of 0.72 and 0.71.Keywords: discovery learning, worksheet, concept mastery. DOI: http://dx.doi.org/10.23960/jpmipa/v20i1.pp7-11